About the Nature of the Spectrum of the Periodic Problem for the Heat Equation with a Deviating Argument - I. Orazov; A. Shaldanbayev; M. Shomanbayeva (Abstract and Applied Analysis)
We study the nature of the spectrum of the periodic problem for the heat equation with a lower-order term and with a deviating argument. A significant influence of the lower-order term on the correct solvability of this problem is found. We obtain a criterion for the strong solvability of the above-mentioned problem.